Induced Variations in Brassinosteroid Genes Define Barley Height and Sturdiness, and Expand the Green Revolution Genetic Toolkit . Issue 4 (20th October 2014) - Dockter, Christoph; Gruszka, Damian; Braumann, Ilka; Druka, Arnis; Druka, Ilze; Franckowiak, Jerome; Gough, Simon P.; Janeczko, Anna; Kurowska, Marzena; Lundqvist, Joakim; Lundqvist, Udda; Marzec, Marek; et al.
Abstract : Historic barley short-culm mutants deficient in brassinosteroid genes are attractive targets for development of lodging-resistant crop plants . Abstract: Reduced plant height and culm robustness are quantitative characteristics important for assuring cereal crop yield and quality under adverse weather conditions. A very limited number of short-culm mutant alleles were introduced into commercial crop cultivars during the Green Revolution. We identified phenotypic traits, including sturdy culm, specific for deficiencies in brassinosteroid biosynthesis and signaling in semidwarf mutants of barley ( Hordeum vulgare ). This set of characteristic traits was explored to perform a phenotypic screen of near-isogenic short-culm mutant lines from the brachytic, breviaristatum, dense spike, erectoides, semibrachytic, semidwarf, and slender dwarf mutant groups. In silico mapping of brassinosteroid-related genes in the barley genome in combination with sequencing of barley mutant lines assigned more than 20 historic mutants to three brassinosteroid-biosynthesis genes ( BRASSINOSTEROID - 6 - OXIDASE, CONSTITUTIVE PHOTOMORPHOGENIC DWARF, and DIMINUTO ) and one brassinosteroid-signaling gene ( BRASSINOSTEROID - INSENSITIVE1 [ HvBRI1 ]). Analyses of F2 and M2 populations, allelic crosses, and modeling of nonsynonymous amino acid exchanges in protein crystal structures gave a further understanding of the control of barley plant architecture and sturdiness by brassinosteroid-related genes. Alternatives to the widely used but highly temperature-sensitive uzu1.a allele of HvBRI1 represent potential genetic building blocks for breeding strategies with sturdy and climate-tolerant barley cultivars.